Perlindungan Hukum Terhadap Keselamatan Kerja Wanita (Studi Kasus Pada Pekerja Wanita di Usaha Hiburan Malam Kota Surabaya) - Dewananta Julyan Saputra (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this study is to discuss and analyze the employment agreement in relation to the legal protection of women workers working in nightlife businesses in the city of Surabaya in terms of Law of the Republic of Indonesia Number 13 of 2003 concerning Manpower and discuss and analyze the legal protection of women's safety in the nightlife business in the city of Surabaya in terms of Law of the Republic of Indonesia Number 13 of 2003 concerning Employment. This research is included in research with a juridical approach. The results showed that the employment agreement in relation to the legal protection of women workers working in nightlife businesses in the city of Surabaya in terms of Law of the Republic of Indonesia Number 13 of 2003 concerning Manpower showed that based on Article 76 of Law Number 13 of 2003 concerning Manpower and the Decree of the Minister of Manpower and Transmigrasai Number 224 of 2003 emphasized more legal protection for women working in At night by guaranteeing and providing all the rights that need to be obtained by these women workers. The results also show that legal protection for women's safety in nightlife businesses in Surabaya City is reviewed from Law of the Republic of Indonesia Number 13 of 2003 concerning Manpower based on agreement issues, providing nutritious food and drinks, transportation problems, lighting problems in night workplaces, as well as protection against crime, safety and decency.